2004
DOI: 10.1002/14651858.cd001776.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen-releasing intrauterine systems versus other forms of reversible contraceptives for contraception

Abstract: Progestogen-releasing intrauterine systems versus other forms of reversible contraceptives for contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 60 publications
0
11
1
2
Order By: Relevance
“…Breast tenderness following the use of the levonorgestrelreleasing intrauterine device has been reported in 11 -36% of users (French et al 2010;Kittelsen and Istre 1998). In our study, de novo breast tenderness was reported in 20% of women, although 72% of those who complained of breast tenderness before treatment reported that it had improved or disappeared.…”
Section: Vaughan and P Byrnecontrasting
confidence: 42%
“…Breast tenderness following the use of the levonorgestrelreleasing intrauterine device has been reported in 11 -36% of users (French et al 2010;Kittelsen and Istre 1998). In our study, de novo breast tenderness was reported in 20% of women, although 72% of those who complained of breast tenderness before treatment reported that it had improved or disappeared.…”
Section: Vaughan and P Byrnecontrasting
confidence: 42%
“…The copper IUD has a reported failure rate at 1 year of 0.8%, and a 10-year failure rate comparable to female sterilization of 1.9 per 100 12. A Cochrane Review evaluating 21 randomized trials concluded that the effectiveness of the LNG-20 IUD is similar to the copper IUD;13 other studies have shown the LNG-20 IUD to be among the most effective contraceptive methods, with a failure rate of 0.1% at 1 year and 0.5% at 5 years, similar to or better than female sterilization 14. Clinical trials of the LNG-14 IUD yielded similar results, showing a cumulative pregnancy rate of 0.9% over 3 years 15…”
Section: Efficacymentioning
confidence: 99%
“…However, according to two Cochrane Reviews, few studies have been published on this topic (10, 11). Furthermore, those that have been published found conflicting results.…”
Section: Introductionmentioning
confidence: 99%